Trends in Honey Purchase and Consumption in Trás-Os-Montes Region, Portugal - Ribeiro, Maria Isabel Barreiro; Fernandes, Antonio Jose Gonsalves; Cabo, Paula Sofia Alves do; Diniz, Francisco Jose Lopes de Sousa (Economy of Regions, 2019)
Honey is considered the only food of animal origin that can be consumed without being processed. The literature presents several reasons why people consume honey, namely, it being a natural and healthy product known for its dietary, nutritional and medicinal characteristics. Moreover, other reasons for honey’s purchase include the product quality; the region of origin; the information available on the product’s label, the brand’s reputation; and the variety, texture, taste, aroma, appearance, packaging and price of honey. Thus, we intend to identify determinant factors on which consumers base their purchasing decision. Therefore, we developed a cross-sectional study based on a non-probabilistic sample of 474 individuals, 399 of whom were honey consumers. We collected the data in the period from March to May 2016 using a questionnaire [1], which we applied directly to consumers in the city of Braganca. Later, we analysed the data with SPSS 23.0 software. The data analysis included a univariate descriptive analysis and a multivariate analysis that involved assessment of a binary logistic regression in order to identify the determinant factors for purchasing and consuming honey. The statistically significant parameters included taste, colour, origin, and certification label, at a significance level of 1 %. These characteristics explained 68.9 % of the consumer’s decision to purchase honey. It is noteworthy that non-consumers considered the certification label important (when purchasing the product to offer to someone), while in the process of decision-making honey consumers valued taste, colour and country of origin.